Commercialization of Lithium Battery Technologies for Electric Vehicles. Issue 27 (6th June 2019) - Zeng, Xiaoqiao; Li, Matthew; Abd El‐Hady, Deia; Alshitari, Wael; Al‐Bogami, Abdullah S.; Lu, Jun; Amine, Khalil
Abstract: The currently commercialized lithium‐ion batteries have allowed for the creation of practical electric vehicles, simultaneously satisfying many stringent milestones in energy density, lifetime, safety, power, and cost requirements of the electric vehicle economy. The next wave of consumer electric vehicles is just around the corner. Although widely adopted in the vehicle market, lithium‐ion batteries still require further development to sustain their dominating roles among competitors. In this review, the authors survey the state‐of‐the‐art active electrode materials and cell chemistries for automotive batteries. The performance, production, and cost are included. The advances and challenges in the lithium‐ion battery economy from the material design to the cell and the battery packs fitting the rapid developing automotive market are discussed in detail. Also, new technologies of promising battery chemistries are comprehensively evaluated for their potential to satisfy the targets of future electric vehicles. Abstract : A detailed discussion on the various aspects of the lithium‐ion battery industry is presented. From raw material cost breakdowns to government mandates, to a brief discussion on the future of Li‐based energy storage systems, the authors draw a clear picture of the high level aspects of this industry.